Physical Qualities of An Athlete As A Subject Of Education At The Initial Stage Of Sports Training - Scientific supervisor: G‘anieva M.Yu.; Student: Azimova S.R. (Genius Journals, 2024)
This article, which is presented, provides information on the general basics of general and special physical training of table tennis players and its development. Also, the importance of general and special physical training in improving the level of physical fitness of table tennis players is highlighted.
Keywords: general physical training; special physical training; training processes